Association Between Immune Activation and Birth Outcomes Among HIV-Infected and Uninfected Pregnant Women in Zambia - Pawlak, Natalie. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Clinical & Translational Science.; Advisors: Christopher Gill, and David Kent.; Committee: Christopher Gill, Donald Thea, Janis Breeze, and David Kent.; Keywords: Immunology, Obstetrics, and Medicine.